Basal Cell Adenocarcinoma of the Minor Salivary Glands Involving Palate and Maxillary Sinus - Sarath,Prathi Venkata; Kannan,N.; Patil,Rajendra; Manne,Rakesh Kumar; Swapna,Beeraka; Suneel Kumar,K. V.
Basal cell adenocarcinoma (BCAC) is a rare neoplasm accounting for only 2.9% of all salivary gland neoplasms. BCAC involving palatal minor salivary glands are exceedingly rare, and only 10 cases have been reported in the literature. The treatment of choice is surgical excision. Here, we report a case of a 55-year-old male patient with massive BCAC of palatal minor salivary gland extending into the maxillary sinus. This is the first case of BCAC treated by radiotherapy followed by chemotherapy. A follow-up check conducted after 14-months showed good prognosis.